Observation of the cabibbo-suppressed decay Ξ+c→pK- π+ - Jun, S. Y.; Akchurin, N.; Andreev, V. A.; Atamantchouk, A. G.; Aykac, M.; Balatz, M. Y.; Bondar, N. F.; Bravar, A.; Cooper, P. S.; Dauwe, L. J.; Davidenko, G. V.; Dersch, U.; et al. (American Physical Society (APS), 2000)
We report the first observation of the Cabibbo-suppressed charm baryon decay Ξ+c→pK- π+. We observe 150±22±5 events for the signal. The data were accumulated using the SELEX spectrometer during the 1996-1997 fixed target run at Fermilab, chiefly from a 600GeV/c Σ- beam. The branching fractions of the decay relative to the Cabibbo-favored Ξ+c→Σ+K-π+ and Ξ+c→Ξ-π+π+ are measured to be B(Ξ+c→pK-π+)/B(Ξ+c→Σ+K-π+)=0.22±0.06±0.03 and B(Ξ+c→pK-π+)/B(Ξ+c→Ξ-π+π+)=0.20±0.04±0.02, respectively. © 2000 The American Physical Society.